THE EFFECTIVENESS OF SELF COLLECTION STRATEGY AND MOTIVATION ON STUDENTS’ ENGLISH VOCABULARY MASTERY - selfa idriani (BASIS (Bahasa dan Sastra Inggris), 2018)
This research purposed to prove whether Self Collection Strategy and Students’ Motivation gives significant effect on the students’ Vocabulary Mastery on English Subject. This research was quasi-experimental research by using the post test-only control group design. The population was the students at Economic Accountant Department Bung Hatta University in the academic year of 2016/2017. The writer used cluster random sampling to select the samples. To collect the data, the researcher used vocabulary test. The data analyzed by using t-test and SPSS 16.0. The findings of this research showed that the mean score of students who were taught by using Self Collection Strategy was 84. The mean score of students who were taught by using memory strategy was 76. It means that Self Collection Strategy gave significant effect toward their vocabulary mastery on English Subject. The elements of Self Collection Strategy such as heterogeneous group, individual accountability, and group reward are considered as the effort for the findings.